Morfometria da fibra muscular peitoral e das vilosidades intestinais de Calidris pusillas (LINNAEUS, 1766) durante o período de invernada no Brasil - Chaves, Felipe de Queiroz (2016)
Migration became a habit among several animal such as birds of the order Charadriiformes. Investigations of this group are necessary owing to the lack of information about major aspects to the physiology of migration. In the present study were analyzed the effects of migration in morphology of the specie Calidris pusilla which migrates to Brazil during winter, arriving at September or October and coming back between March and May to reproductive areas. Specimens captured from coast of the Paraíba had have removed a fragment of the pectoral muscles. It was fixed in 10% formaldehyde and processed for histological practices following pattern procedures. Expressive differences were found during the time that these birds stayed in Brazil, including increased diameter of pectoral muscle fibers, and initial reduction followed by subsequent increase of intestinal villus. Otherwise intestinal crypts increased their depth in the first half of wintering with a decrease in the second half. When it was evaluated the index of intestinal goblet cells, there were no significant variations. It can be concluded that histomorphometric changes occur that make these birds adapted to the different moments of the migration.